209 Increased burden of headache in patients with migraine complicated by MOH: sub-group analysis BECOME study. Issue 6 (27th May 2022) - Panesar, Pritpal; Watson, David; Pozo-Rosich, Patricia; Lucas, Christian; Gaul, Charly; Ramsden, Emma; Ritter, Shannon; Martelletti, Paolo; Snellman, Josefin
Abstract : Objective: To evaluate the burden of headache in patients with chronic migraine complicated by medi- cation overuse headache (CM+MO) using patient-reported outcomes (PRO) and healthcare resource utilisation (HRU) questionnaires. Methods: BECOME was a prospective, non-interventional study conducted in 2 concurrent parts over 3 months across Europe and Israel. Part 1 assessed clinical characteristics of all patients with migraine visiting headache specialist centres over 3 months. Part 2 examined burden of disease in patients with ≥1 prior prophylactic treatment failure (PPTF), ≥4 monthly migraine days (MMD). We assessed quality of life (QoL) in patients in Part 2 using PRO questionnaires. Results: Of the 2419 patients (86.9% females; mean[SD] age 43.0[11.56] years) analysed in Part 2, 571 (23.6%) reported CM+MO. Patients with CM+MO reported lower functioning (mean[SD] EQ-5D utility scores 0.67[0.24] vs 0.78[0.21]), lower health status (EQ VAS scores 59.3[20.94] vs 69.8[19.48]), higher dis- ability (mMIDAS score 35.5[21.98] vs 21.9[17.39]) and greater proportion had grade IV disability (88.1% vs 80.1%) than those without MO. Conclusions: Patients with ≥1 PPTF reported severe burden of migraine irrespective of MO, but patients with MO had lower functioning and health status, greater severity in disability, and greater use of HRU than those without MO. pritpal.panesar@novartis.com